PENINGKATAN PENANAMAN BUDAYA MELAYU JAMBI UNTUK MEMBENTUK KARAKTER GENERASI MUDA - Nelly Indrayani; Supian Supian (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
Several Malay cultures resulted from the interactional pattern of community activities. Such Malay culture becomes an identity for the people adhering to it. This identity is its adherents’ different from other cultural adherents. However, corresponding to current demand and cultural dynamic from time to time, Malay cultural identity as this identity cannot always be understood by the younger generation partially or even entirely. Especially, young generation today has been heavily involved in technological developments. This community service aims to foster awareness of Malay culture, and to instill the character of Malay culture to the young generation. The methods used in this activity were dialogue and lecture, and interview methods with a socio-cultural approach. These method and approach were expected to raise awareness of the preservation of Malay culture among young generation which is not only abstract and embodied into ideas, but can also be expressed in behavior reflected by the young generation that will shape its cultural character.